Changes in serum cytokine levels, hepatic and intestinal morphology in aflatoxin B1-induced injury: modulatory roles of melatonin and flavonoid-rich fractions from Chromolena odorata (2015)
Aflatoxins are known to produce chronic carcinogenic, mutagenic, and teratogenic effects, as well as acute inflammatory effects, especially in the gastrointestinal tract. The potentials of the flavonoid-rich extract from Chromolena odorata (FCO) and melatonin (a standard anti-oxidant and anti-inflammatory agent) against aflatoxin B1 (AFB1)-induced alterations in pro-inflammatory cytokine levels and morphology of liver and small intestines were evaluated in this study. We utilized Wistar albino rats (200–230 g) randomly divided into five groups made up of group A, control rats; group B, rats given AFB1 (2.5 mg/kg, intraperitone al) twice on days 5 and 7; rats in groups C, D, and E were treated with melatonin (10 mg/kg, intraperitoneal) or oral doses of FCO1 (50 mg/kg) and FCO2 (100 mg/kg) for 7 days, respectively, along with AFB1 injection on days 5 and 7. Serum levels of interleukin 1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α) were determined using commercial ELISA kits and histopathological evaluation of the liver, duodenum, and ileum were also carried out. We observed significant elevation (p < 0.05) in serum IL-1β correlating with hemorrhages and leucocytic and lymphocytic infiltration in the liver and intestines as evidences of an acute inflammatory response to AFB1 administration. All treatments yielded significant reduction (p < 0.05) in IL-1β levels, although TNF-α levels were not significantly altered in all rats that received AFB1, irrespective of the treatments. Melatonin and FCO2 produced considerable protection of hepatic tissues, although melatonin was not quite effective in protecting the intestinal lesions. Our findings suggest a modulation of cytokine expression that may, in part, be responsible for the abilities of C. odorata or melatonin in amelioration of hepatic and intestinal lesions associated with aflatoxin B1 injury.